A lithium ion battery
By using PVDF glue-coated separator and non-aqueous electrolyte of the compound of Structural Formula 1 in high-pressure lithium-ion batteries, the problem of insufficient residual amount of electrolyte is solved, the circulation and high temperature performance of the battery are improved, and the battery is achieved higher battery stability.
Patent Information
- Application Number
- CN202011467307.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-12-14
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2040-12-14
AI Technical Summary
The low porosity in high-pressure lithium-ion batteries leads to insufficient residual amount of electrolyte, affecting circulation performance, and increasing the amount of electrolyte can easily lead to high-temperature performance deterioration.
The compound of Structural Formula 1 in the glue coating separator containing PVDF and the non-aqueous electrolyte is used to promote the swelling of the glue coating layer through the hot pressing process, absorb more electrolyte, increase the battery liquid retention capacity, and maintain battery performance at high temperatures.
It effectively improves the battery's circulation performance and high-temperature storage performance, reduces the free electrolyte, avoids the battery's gas production and expansion rate at high temperatures, and improves the battery's high-temperature circulation performance.
Smart Images

Figure CN114628773B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to a lithium ion battery. Background Art
[0002] Lithium-ion batteries have been widely used in 3C digital products such as mobile phones and laptops, as well as new energy vehicles, due to their high operating voltage, wide operating temperature range, high energy density and power density, no memory effect and long cycle life. In recent years, with the continuous development of 3C digital products becoming thinner and lighter, and the battery industry increasingly requiring lithium-ion batteries to have high energy density, digital batteries tend to be thin-layer batteries with high energy density.
[0003] Under this market trend, digital batteries tend to use high-density, low-porosity positive and negative electrodes and thin-layer separators. In order to enhance the mechanical strength of the battery and also to avoid short circuits between the high-density positive and negative electrodes due to puncture or lithium dendrites, PVDF coated separators are used in large quantities to reduce the safety risks caused by battery cycle deformation or external puncture. However, in this battery system, the porosity is very low, and the PVDF coated separator has insufficient affinity for the electrolyte. The amount of electrolyte absorbed is small, resulting in insufficient residual electrolyte during the battery manufacturing process, serious battery cycle performance problems and lithium precipitation problems. If the residual electrolyte of the battery is forcibly increased, the free electrolyte in the battery will increase. Under high temperature conditions, the electrolyte will react with the positive and negative electrodes, and the gas production will increase, resulting in deterioration of high-temperature storage performance.
[0004] There are currently two ways to solve this problem in the electrolyte. One is to add low-viscosity solvents, such as ethyl acetate, which can reduce the viscosity of the electrolyte, promote electrolyte infiltration, and improve the battery's cycle, rate and other performance; the other is to add additives that promote circulation and reduce impedance, such as FEC, which will reduce battery impedance, make the battery less likely to precipitate lithium, and help improve the battery's cycle life. However, both methods will reduce the high-temperature stability of the battery, resulting in poor high-temperature performance of the electrolyte and easy bloating. Therefore, for high-density, low-porosity battery systems, how to improve the cycle performance without degrading the high-temperature performance of the battery is an urgent problem that the industry needs to solve. Summary of the invention
[0005] Aiming at the problem that the existing high-pressure lithium-ion batteries have insufficient liquid storage capacity and thus affect the battery cycle performance, the present invention provides a lithium-ion battery.
[0006] The technical solution adopted by the present invention to solve the above technical problems is as follows:
[0007] The present invention provides a lithium ion battery, comprising a positive electrode, a negative electrode, a glue-coated separator and a non-aqueous electrolyte, wherein the positive electrode comprises a positive electrode material layer, the compaction density of the positive electrode material layer is 3.3 g / cc to 4.3 g / cc, the negative electrode comprises a negative electrode material layer, the compaction density of the negative electrode material layer is 1.55 to 1.85 g / cc, the glue-coated separator comprises a porous substrate and a glue-coated layer disposed on at least one side of the porous substrate, the glue-coated layer comprises PVDF, and the non-aqueous electrolyte comprises a solvent, an electrolyte salt and a compound shown in structural formula 1:
[0008]
[0009] Structural formula 1
[0010] Wherein, n = 0 to 2; R 1-(5+n) Each is independently selected from H, halogen or C1-C10 substituted or unsubstituted alkyl.
[0011] Optionally, the compound shown in structural formula 1 includes one or more of cyclopentane, cyclohexane, cycloheptane, methylcyclopentane, ethylcyclopentane, 1,3-dimethylcyclopentane, 1,4-dimethylcyclopentane, methylcyclohexane, ethylcyclohexane, propylcyclohexane, butylcyclohexane, pentylcyclohexane, cis-1-methyl-3-ethylcyclohexane, trans-1-methyl-3-ethylcyclohexane, 1,3-dimethylcyclohexane, 1,4-dimethylcyclohexane, 1,3,5-trimethylcyclohexane, bromocyclohexane, 1-chloro-2-ethylcyclohexane and perfluoro(ethylcyclohexane).
[0012] Optionally, based on the total mass of the non-aqueous electrolyte being 100%, the added amount of the compound represented by structural formula 1 is 0.001 to 5%.
[0013] Optionally, the surface energy of the glue-coated diaphragm is ≥25 mN / m;
[0014] The porous substrate is selected from high molecular polymer porous materials.
[0015] Optionally, the positive electrode material layer includes a positive electrode active material, and the positive electrode active material is selected from LiNi x Co y M z O2, wherein M is selected from one of Mn and Al, and 0<x≤1, 0<y≤1, 0<z≤1, x+y+z=1, the compaction density of the positive electrode material layer is 3.4g / cc~3.7g / cc, and the porosity of the positive electrode material layer is ≤30%.
[0016] Optionally, the positive electrode material layer includes a positive electrode active material, the positive electrode active material is selected from LiCoO2, the compaction density of the positive electrode material layer is 4.1 g / cc to 4.3 g / cc, and the porosity of the positive electrode material layer is ≤30%.
[0017] Optionally, the compaction density of the negative electrode material layer is 1.7-1.85 g / cc, the porosity of the negative electrode material layer is ≤30%, the negative electrode material layer includes a negative electrode active material, the negative electrode active material has a layered crystal structure, and the crystal interlayer spacing of the negative electrode active material is 0.32-0.36 nm.
[0018] Optionally, the solvent includes one or more of cyclic carbonates, linear carbonates, carboxylates and ethers.
[0019] Optionally, the electrolyte salt includes one or more of LiPF6, LiPO2F2, LiBF4, LiBOB, LiClO4, LiCF3SO3, LiDFOB, LiN(SO2CF3)2 and LiN(SO2F)2;
[0020] In the non-aqueous electrolyte, the concentration of the electrolyte salt is 0.5M-3.5M.
[0021] Optionally, the non-aqueous electrolyte further comprises an auxiliary additive, wherein the auxiliary additive comprises one or more of a fluorinated cyclic carbonate, an unsaturated cyclic carbonate, a cyclic sulfonate and a nitrile compound;
[0022] Based on the total mass of the non-aqueous electrolyte being 100%, the amount of the auxiliary additive added is 0.001-5%.
[0023] Optionally, the fluorinated cyclic carbonate includes fluorinated ethylene carbonate;
[0024] The unsaturated cyclic carbonate includes 1,3-propane sultone and / or vinylene carbonate;
[0025] The cyclic sulfonate ester includes vinyl sulfate;
[0026] The nitrile compound includes one or more of succinonitrile, adiponitrile, ethylene glycol bis(propionitrile) ether, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebaconitrile.
[0027] According to the high-density lithium-ion battery provided by the present invention, a coated diaphragm containing PVDF and a non-aqueous electrolyte containing a compound shown in structural formula 1 are used. The inventors accidentally discovered through experiments that in a battery containing high-density positive and negative electrode material layers, a hot pressing formation process is adopted. During the high-temperature formation process, the compound shown in structural formula 1 in the non-aqueous electrolyte can effectively promote the swelling of the coated layer containing PVDF on the coated diaphragm, thereby absorbing more free electrolyte, increasing the battery's liquid retention capacity, and further improving the battery's cycle performance. In addition, the PVDF polymer swells and absorbs more electrolyte, so the free electrolyte becomes less, and even if the residual liquid amount is increased, it can be promptly adsorbed by the coated diaphragm, and the battery's high-temperature storage performance will not be deteriorated. DETAILED DESCRIPTION
[0028] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0029] The present invention provides a lithium ion battery, comprising a positive electrode, a negative electrode, a glue-coated separator and a non-aqueous electrolyte, wherein the positive electrode comprises a positive electrode material layer, the compaction density of the positive electrode material layer is 3.3 g / cc to 4.3 g / cc, the negative electrode comprises a negative electrode material layer, the compaction density of the negative electrode material layer is 1.55 to 1.85 g / cc, the glue-coated separator comprises a porous substrate and a glue-coated layer disposed on at least one side of the porous substrate, the glue-coated layer comprises PVDF, and the non-aqueous electrolyte comprises a solvent, an electrolyte salt and a compound shown in structural formula 1:
[0030]
[0031] Structural formula 1
[0032] Wherein, n = 0 to 2; R 1-(5+n) Each is independently selected from H, halogen or C1-C10 substituted or unsubstituted alkyl.
[0033] The lithium-ion battery uses a coated diaphragm containing PVDF and a non-aqueous electrolyte containing a compound shown in structural formula 1. The inventor unexpectedly discovered through experiments that in a battery containing high-density positive and negative electrode material layers, a hot pressing formation process is adopted. During the high-temperature formation process, the compound shown in structural formula 1 in the non-aqueous electrolyte can effectively promote the swelling of the coated layer containing PVDF on the coated diaphragm, thereby absorbing more free electrolyte, increasing the battery's liquid retention capacity, and further improving the battery's cycle performance. In addition, the PVDF polymer swells and absorbs more electrolyte, so the free electrolyte becomes less, and even if the residual liquid amount is increased, it can be promptly adsorbed by the coated diaphragm, and the high-temperature performance of the battery will not be deteriorated.
[0034] In some embodiments, the halogen includes F, Cl, Br, I.
[0035] In some embodiments, the compound represented by structural formula 1 includes one or more of cyclopentane, cyclohexane, cycloheptane, methylcyclopentane, ethylcyclopentane, 1,3-dimethylcyclopentane, 1,4-dimethylcyclopentane, methylcyclohexane, ethylcyclohexane, propylcyclohexane, butylcyclohexane, pentylcyclohexane, cis-1-methyl-3-ethylcyclohexane, trans-1-methyl-3-ethylcyclohexane, 1,3-dimethylcyclohexane, 1,4-dimethylcyclohexane, 1,3,5-trimethylcyclohexane, bromocyclohexane, 1-chloro-2-ethylcyclohexane and perfluoro(ethylcyclohexane).
[0036] It should be noted that the specific material selection of the compound shown in the above structural formula 1 is only a preferred compound in the present application and should not be construed as a limitation to the present invention.
[0037] In some embodiments, based on the total mass of the non-aqueous electrolyte being 100%, the added amount of the compound represented by Structural Formula 1 is 0.001-5%.
[0038] In a preferred embodiment, based on the total mass of the non-aqueous electrolyte being 100%, the added amount of the compound represented by structural formula 1 is 3-5%.
[0039] In the battery system provided by the present invention, when the amount of the compound shown in Structural Formula 1 added in the non-aqueous electrolyte is within the above-mentioned range, it can effectively ensure the improvement of the swelling performance of the PVDF coating layer, thereby improving the high-temperature cycle effect and high-temperature storage effect of the battery; when the amount of the compound shown in Structural Formula 1 added is too low, the performance improvement of the battery is not obvious; when the amount of the compound shown in Structural Formula 1 added is too high, the side reactions inside the battery will increase, the battery impedance will increase, and the battery cycle performance will deteriorate.
[0040] In different embodiments, based on the total mass of the non-aqueous electrolyte as 100%, the added amount of the compound represented by structural formula 1 can be selected from the following values: 0.001%, 0.01%, 0.05%, 0.1%, 0.3%, 0.6%, 0.8%, 1%, 1.3%, 1.5%, 1.8%, 2.1%, 2.5%, 2.9%, 3%, 3.4%, 3.7%, 3.9%, 4.1%, 4.4%, 4.7%, 5%.
[0041] In some embodiments, the surface energy of the rubber-coated diaphragm is ≥ 25 mN / m.
[0042] If the surface energy of the coated membrane is lower than 25 mN / m, it is difficult for the electrolyte to infiltrate the coated membrane, which is not conducive to the application of the coated membrane and the non-aqueous electrolyte in high-density low-porosity batteries.
[0043] In some embodiments, the porous substrate is selected from high molecular polymer porous materials.
[0044] In some embodiments, the porous substrate is a single-layer porous polymer material or a combination of multiple layers of porous polymer materials.
[0045] In a preferred embodiment, the porous substrate is selected from one or more of polyolefin membranes, polyamide membranes, polysulfone membranes, polyphosphazene membranes, polyethersulfone membranes, polyetheretherketone membranes, polyetheramide membranes and polyacrylonitrile membranes.
[0046] Specifically, the porous substrate is selected from polyethylene or polypropylene materials.
[0047] It should be noted that the combination of the coated diaphragm and the non-aqueous electrolyte provided by the present invention is particularly suitable for application in high-pressure compaction and low-porosity batteries. The inventors have found through experiments that when the above-mentioned combination of the coated diaphragm and the non-aqueous electrolyte is applied to high-pressure compaction and low-porosity batteries, it can effectively solve the long-standing problem of insufficient high-temperature cycle performance of high-pressure compaction and low-porosity batteries.
[0048] It should be noted that, in different embodiments, the positive electrode active material in the positive electrode material layer can be selected from different materials, and correspondingly, the compaction density of the positive electrode material layer also varies.
[0049] In some embodiments, the positive electrode material layer includes a positive electrode active material, and the positive electrode active material is selected from LiNi x Co y M z O2, wherein M is selected from one of Mn and Al, and 0<x≤1, 0<y≤1, 0<z≤1, x+y+z=1, the compaction density of the positive electrode material layer is 3.4g / cc~3.7g / cc, and the porosity of the positive electrode material layer is ≤30%.
[0050] In some embodiments, the positive electrode active material is selected from LiCoO2, the compaction density of the positive electrode material layer is 4.1 g / cc to 4.3 g / cc, and the porosity of the positive electrode material layer is ≤30%.
[0051] In a preferred embodiment, the positive electrode active material is selected from LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.5 Co 0.3 Mn 0.2O2 or LiCoO2.
[0052] In some embodiments, the positive electrode material layer further includes a positive electrode conductor and a positive electrode binder.
[0053] In some embodiments, the positive electrode further includes a positive electrode current collector for drawing current, and the positive electrode material layer is attached to the positive electrode current collector.
[0054] The positive electrode current collector can be selected from various existing metal materials. In a preferred embodiment, the positive electrode current collector is selected from aluminum foil.
[0055] In some embodiments, the porosity of the negative electrode material layer is ≤30%, the negative electrode material layer includes a negative electrode active material, the negative electrode active material has a layered crystal structure, and the crystal interlayer spacing of the negative electrode active material is 0.32-0.36 nm.
[0056] In a preferred embodiment, the negative electrode active material is selected from one or more of artificial graphite and natural graphite.
[0057] In some embodiments, the negative electrode material layer further includes a negative electrode conductor and a negative electrode binder.
[0058] In some embodiments, the negative electrode further includes a negative electrode current collector for drawing current, and the negative electrode material layer is attached to the negative electrode current collector.
[0059] The negative electrode current collector can be selected from various existing metal materials. In a preferred embodiment, the negative electrode current collector is selected from copper foil.
[0060] In some embodiments, the solvent includes one or more of cyclic carbonates, linear carbonates, carboxylates, and ethers.
[0061] In some embodiments, the electrolyte salt includes one or more of LiPF6, LiPO2F2, LiBF4, LiBOB, LiClO4, LiCF3SO3, LiDFOB, LiN(SO2CF3)2, and LiN(SO2F)2;
[0062] In the non-aqueous electrolyte, the concentration of the electrolyte salt is 0.5M-3.5M.
[0063] In some embodiments, the non-aqueous electrolyte further includes an auxiliary additive, and the auxiliary additive includes one or more of a fluorinated cyclic carbonate, an unsaturated cyclic carbonate, a cyclic sulfonate, and a nitrile compound.
[0064] In some embodiments, based on the total mass of the non-aqueous electrolyte being 100%, the amount of the auxiliary additive added is 0.001-5%.
[0065] In some embodiments, the fluorinated cyclic carbonate comprises fluorinated ethylene carbonate;
[0066] The unsaturated cyclic carbonate includes 1,3-propane sultone and / or vinylene carbonate;
[0067] The cyclic sulfonate ester includes vinyl sulfate;
[0068] The nitrile compound includes one or more of succinonitrile, adiponitrile, ethylene glycol bis(propionitrile) ether, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebaconitrile.
[0069] The present invention is further described below by way of examples.
[0070] Example 1
[0071] This embodiment is used to illustrate the lithium ion battery and the preparation method thereof disclosed in the present invention, and includes the following steps:
[0072] 1) Preparation of electrolyte
[0073] Ethylene carbonate (EC) and diethyl carbonate (DEC) were mixed at a mass ratio of EC:DEC=3:7, and then lithium hexafluorophosphate (LiPF6) was added to a molar concentration of 1 mol / L, and then a certain mass of the compound shown in structural formula 1 was added according to Table 1.
[0074] 2) Preparation of positive electrode
[0075] The positive electrode active material LiCoO2, the conductive carbon black Super-P and the binder polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 93:4:3, and then dispersed in N-methyl-2-pyrrolidone (NMP) to obtain a positive electrode slurry. The slurry was evenly coated on both sides of the aluminum foil, and after drying, rolling and vacuum drying, a positive electrode with a compaction density as shown in Table 1 was obtained, and an aluminum lead wire was welded with an ultrasonic welder to obtain a positive electrode plate with a thickness of 120-150μm.
[0076] 3) Preparation of negative electrode plate
[0077] The negative electrode active material artificial graphite, conductive carbon black Super-P, binder styrene butadiene rubber (SBR) and carboxymethyl cellulose (CMC) were mixed in a mass ratio of 94:1:2.5:2.5, and then dispersed in deionized water to obtain a negative electrode slurry. The negative electrode slurry was coated on both sides of the copper foil, and after drying, rolling and vacuum drying, a negative electrode with a compaction density as shown in Table 1 was obtained, and a nickel lead wire was welded with an ultrasonic welder to obtain a negative electrode plate, and the thickness of the plate was 120-150 μm.
[0078] 4) Preparation of battery cells
[0079] A PVDF-coated separator is placed between the positive plate and the negative plate, respectively. The sandwich structure consisting of the positive plate, the negative plate and the coated separator is then wound. The wound body is flattened and placed in an aluminum foil packaging bag. The battery is vacuum-baked at 75°C for 48 hours to obtain a battery cell ready for liquid injection.
[0080] 5) Battery filling, formation and secondary sealing
[0081] In a glove box with water and oxygen content <10 ppm, the prepared electrolyte was injected into the battery cell, vacuum packaged, and left to stand for 24 hours.
[0082] The hot pressing process was adopted, with a temperature of 75 degrees Celsius and a pressure of 0.8MPa. The battery was charged at 0.1C constant current for 45min, 0.2C constant current for 30min, and then 0.5C constant current for 75min. The battery was vacuum sealed for the second time, and then further charged at a constant current and voltage of 0.2C to the charging cut-off voltage, with a cut-off current of 0.03C, and discharged at a constant current of 0.2C to 3.0V.
[0083] Embodiments 2 to 25
[0084] Examples 2 to 25 are used to illustrate the lithium ion battery and the preparation method thereof disclosed in the present invention, and include most of the operating steps in Example 1, except that:
[0085] The positive electrode active material and the charge cut-off voltage of the formation, the compaction density of the positive electrode material layer and the negative electrode material layer are shown in Examples 2 to 25 in Table 1.
[0086] In the electrolyte, based on the total mass of the electrolyte being 100%, the compounds represented by the structural formula 1 shown in Examples 2 to 25 in Table 1 and other additives were added respectively.
[0087] Comparative Examples 1 to 14
[0088] Comparative Examples 1 to 14 are used to illustrate the lithium ion battery and the preparation method thereof disclosed in the present invention, and include most of the operating steps in Example 1, except that:
[0089] The positive electrode active material and the charge cut-off voltage of the formation, the separator, the compaction density of the positive electrode material layer and the compaction density of the negative electrode material layer are shown in Table 1 for Comparative Examples 1 to 14.
[0090] In the electrolyte, based on the total mass of the electrolyte being 100%, the compounds represented by the structural formula 1 shown in Comparative Examples 1 to 14 in Table 1 and other additives were added respectively.
[0091] Performance Testing
[0092] The lithium ion batteries prepared in the above Examples 1 to 25 and Comparative Examples 1 to 14 were subjected to the following performance tests:
[0093] Residual liquid test
[0094] Measure the mass of the dry cell before liquid injection, measure the mass of the cell again after secondary sealing, and then calculate the residual liquid in the cell according to the following formula:
[0095] Residual liquid (g / Ah) = (cell mass after secondary sealing - dry cell mass) / cell capacity
[0096] High temperature cycle performance test
[0097] The battery was placed in an oven at a constant temperature of 45°C, charged at a constant current of 0.7C to the charge cut-off voltage, then charged at a constant voltage until the current dropped to 0.03C, and then discharged at a constant current of 1C to 3.0V. After N cycles of charge / discharge, the capacity retention rate after the 400th cycle was calculated to evaluate its high temperature cycle performance.
[0098] The capacity retention rate calculation formula for 400 cycles at 45℃ 0.7C / 1C is as follows:
[0099] Nth cycle capacity retention rate (%) = Nth cycle discharge capacity / 1st cycle discharge capacity * 100%;
[0100] High temperature storage test
[0101] The formed battery was charged at room temperature with 1C constant current and constant voltage to the charging cut-off voltage, the cut-off current was 0.03C, and the initial discharge capacity, initial battery thickness and initial internal resistance of the battery were measured. Then, after being fully charged and stored at 60℃ for 30 days, it was discharged at 1C to 3V, and the battery retention capacity and battery thickness after storage were measured. The calculation formula is as follows:
[0102] Battery capacity retention rate (%) = retention capacity / initial capacity × 100%;
[0103] Thickness expansion rate (%) = (battery thickness after storage - initial battery thickness) / initial battery thickness × 100%;
[0104] The test results obtained are entered in Table 1.
[0105] Table 1
[0106]
[0107]
[0108]
[0109] It can be seen from the test results of Examples 1 to 25 and Comparative Examples 1 to 14 that, compared with other embodiments, the combination of the compound shown in Structural Formula 1 and the coated diaphragm containing PVDF provided by the present invention and its application in a battery with a high compaction density has a higher capacity retention rate and a lower expansion rate at high temperature, indicating that the combination provided by the present invention can improve the electrolyte absorption rate of the coated diaphragm, thereby absorbing free electrolyte when the residual liquid amount in the battery is high, reducing the gas production of the battery at high temperature, reducing the battery expansion rate, and effectively improving the high temperature cycle performance and high temperature storage performance of the high compaction density battery.
[0110] By comparing the test results of Examples 3 to 8 and 22, it can be seen that with the increase in the addition amount of the compound represented by Structural Formula 1, the high-temperature cycle performance and high-temperature storage performance of the battery first increase and then decrease, indicating that within the preferred range of the present invention, the compound represented by Structural Formula 1 has the best matching effect with the coated diaphragm containing PVDF, and the addition of excessive or insufficient amounts of the compound represented by Structural Formula 1 is not conducive to the improvement of its battery performance.
[0111] By comparing the test results of Examples 6 and 9 to 12, 18 and 21, it can be seen that in the battery system provided by the present invention, the additional addition of SN, FEC, VC, PS or a combination thereof can further enhance the battery performance.
[0112] By comparing the test results of Examples 13 to 15 with Comparative Examples 1 and 2, it can be seen that the combination of the electrolyte containing the compound represented by Structural Formula 1 and the coated diaphragm containing PVDF provided by the present invention is universally applicable to improving the performance of high compaction density positive and negative electrode material batteries.
[0113] By comparing the test structures of Examples 16 to 21, it can be seen that even if the residual liquid amount of the battery is increased, the high temperature performance of the battery is not significantly deteriorated, indicating that the compound shown in Structural Formula 1 can effectively increase the absorption of the free electrolyte by the coated diaphragm containing PVDF, thereby improving the high temperature performance of the battery.
[0114] From the test results of Comparative Example 16 and Comparative Examples 13 and 14, it can be seen that compared with batteries with low compaction density, the combination of the electrolyte containing the compound shown in Structural Formula 1 and the coated diaphragm containing PVDF provided by the present invention can better reflect its performance improvement effect in batteries with high compaction density, while the performance improvement of this combination is not obvious in batteries with low compaction density.
[0115] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A lithium ion battery, characterized in that: The invention comprises a positive electrode, a negative electrode, a coated separator and a non-aqueous electrolyte, wherein the positive electrode comprises a positive electrode material layer, the positive electrode material layer comprises a positive electrode active material, the positive electrode active material is selected from LiCoO2, the compaction density of the positive electrode material layer is 4.1 g / cc to 4.3 g / cc, and the porosity of the positive electrode material layer is ≤30%; or, the positive electrode active material is selected from LiNi x Co y M z O2, wherein M is selected from one of Mn and Al, and 0<x≤1, 0<y≤1, 0<z≤1, x+y+z=1, the compacted density of the positive electrode material layer is 3.4g / cc~3.7g / cc, and the porosity of the positive electrode material layer is ≤30%; the negative electrode includes a negative electrode material layer, the compacted density of the negative electrode material layer is 1.55-1.85g / cc, the coated separator includes a porous substrate and a coating layer disposed on at least one side of the porous substrate, the coating layer includes PVDF, and the non-aqueous electrolyte includes a solvent, an electrolyte salt and a compound shown in structural formula 1: Structural formula 1 Where n=0~2; R 1-(5+n) Each is independently selected from H or C1-C10 substituted or unsubstituted alkyl.
2. The lithium-ion battery according to claim 1, characterized in that The compound shown in the structural formula 1 includes one or more of cyclopentane, cyclohexane, cycloheptane, methylcyclopentane, ethylcyclopentane, 1,3-dimethylcyclopentane, 1,4-dimethylcyclopentane, methylcyclohexane, ethylcyclohexane, propylcyclohexane, butylcyclohexane, pentylcyclohexane, cis-1-methyl-3-ethylcyclohexane, trans-1-methyl-3-ethylcyclohexane, 1,3-dimethylcyclohexane, 1,4-dimethylcyclohexane, and 1,3,5-trimethylcyclohexane.
3. The lithium-ion battery according to claim 1, characterized in that Based on the total mass of the non-aqueous electrolyte being 100%, the added amount of the compound represented by structural formula 1 is 0.001-5%.
4. The lithium-ion battery according to claim 1, characterized in that The surface energy of the glue-coated diaphragm is ≥25mN / m; The porous substrate is selected from high molecular polymer porous materials.
5. The lithium-ion battery according to claim 1, characterized in that: The compaction density of the negative electrode material layer is 1.7-1.85 g / cc, the porosity of the negative electrode material layer is ≤30%, the negative electrode material layer includes a negative electrode active material, the negative electrode active material is a layered crystal structure, and the crystal layer spacing of the negative electrode active material is 0.32-0.36 nm.
6. The lithium-ion battery according to claim 1, characterized in that The solvent includes one or more of cyclic carbonates, linear carbonates, carboxylates and ethers.
7. The lithium-ion battery according to claim 1, characterized in that: The electrolyte salt includes one or more of LiPF6, LiPO2F2, LiBF4, LiBOB, LiClO4, LiCF3SO3, LiDFOB, LiN(SO2CF3)2 and LiN(SO2F)2; In the non-aqueous electrolyte, the concentration of the electrolyte salt is 0.5M-3.5M.
8. The lithium-ion battery according to claim 1, characterized in that The non-aqueous electrolyte further comprises an auxiliary additive, wherein the auxiliary additive comprises one or more of a fluorinated cyclic carbonate, an unsaturated cyclic carbonate, a cyclic sulfonate and a nitrile compound; Based on the total mass of the non-aqueous electrolyte being 100%, the amount of the auxiliary additive added is 0.001-5%.
9. The lithium-ion battery according to claim 8, characterized in that: The fluorinated cyclic carbonate includes fluoroethylene carbonate; The unsaturated cyclic carbonate includes 1,3-propane sultone and / or vinylene carbonate; The cyclic sulfonate ester includes vinyl sulfate; The nitrile compound includes one or more of succinonitrile, adiponitrile, ethylene glycol bis(propionitrile) ether, hexanetrinitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebaconitrile.
Citation Information
Patent Citations
Nonaqueous electrolyte solution and nonaqueous electrolyte battery
CN102244294A
Non-aqueous electrolyte secondary battery and non-aqueous electrolyte
CN102479976A
Nonaqueous electrolyte for electrochemical devices
CN1641922A